1979
DOI: 10.1111/j.1096-3642.1979.tb01096.x
|View full text |Cite
|
Sign up to set email alerts
|

The chromosomes of the hystricomorphous family Ctenodactylidae (Rodentia: ?Sciuromorpha) and their bearing on the relationships of the four living genera

Abstract: Karyotype studies support the view that modern genera of the family Ctenodactylidae originated in Africa. Karyotype differences between the genera are less obvious than morphological differences but coincide in relating Massoutiera to Felovia and deriving this line from the Pectinator‐like ancestor which, in turn, was closely related to a Ctenodactylus ancestor. 43% of the chromosomes are standard throughout the family; 25% seem to be very susceptible to fragmentation, translocation and inversion. These change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1980
1980
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…The very close relationship between Massoutiera and Felovia is unsurprising due to their similar morphology. This result is in agreement with the analyses carried out by George (1979George ( , 1985.…”
Section: The Crown Groupsupporting
confidence: 95%
See 4 more Smart Citations
“…The very close relationship between Massoutiera and Felovia is unsurprising due to their similar morphology. This result is in agreement with the analyses carried out by George (1979George ( , 1985.…”
Section: The Crown Groupsupporting
confidence: 95%
“…Wood (1977) suggested that Pectinator spekei seemed derivable from Africanomys and Metasayimys, an opinion with which we agree. As defended by some authors (Jaeger 1971;George 1979George , 1985, Pectinator spekei is the most basal of the living species of Ctenodactylinae. This taxon shares an exclusive common ancestor with the species of the Ihroudia clade and the more derived ctenodactylines.…”
Section: The Genus Africanomysmentioning
confidence: 96%
See 3 more Smart Citations